Pengaruh Stretching Exercise Pada Kualitas Hidup Dan Status Fungsional Lansia Penderita Dm Tipe 2 : Effect of Stretching Exercise on Quality of Life and Functional Status Functional Status of Elderly Patients with Dm Type 2 - Isni Hijriana; Yusnita (Fakultas Keperawatan Universitas Andalas, 2022)
elderly. Various interventions are needed by the elderly to overcome the decline in mobility related to age. The purpose of this study is to identify the effectiveness of stretching exercise on the quality of life and functional status of the elderly with type 2 diabetes mellitus. test group design with one intervention group. The total sample in this study was 30 elderly with type 2 diabetes. The sample was taken using a consecutive sampling technique. The intervention given was stretching exercise for 4 weeks. The Wilcoxon Signed Ranks Test statistical test showed that there was a difference between before and after the stretching exercise intervention on the functional status of the elderly, quality of life, general health dimensions, physical health, and social with a p-value (p=0.00), but there is no relationship on the psychological health and environmental dimension. Based on the results of the study, it can be concluded that stretching exercises can improve physical fitness, muscle mass and joint flexibility which have an impact on functional status and quality of life of the elderly. It is hoped that stretching exercise can be used as one nursing independent treatment to improve the quality of life of and increasing the independence of the elderly through the provision of education and regular physical exercise.